Application of microchip and infrared thermography for monitoring body temperature of beef cattle kept on pasture - Giro, Alessandro; Campos Bernardi, Alberto Carlos de; Barioni Junior, Waldomiro; Lemes, Amanda Prudencio [UNESP]; Botta, Daniela; Romanello, Narian; Barreto, Andrea do Nascimento; Garcia, Alexandre Rossetto (Elsevier B.V., 2019)
The monitoring of body temperature is important for the diagnosis of the physiological state of the animal, being dependent on available methods and their applicability within production systems. This work evaluated techniques to monitor the body temperature of beef cattle kept on pasture and their ability to predict internal temperature. Twenty-three adult bovine females were monitored for six months, and collection data carried out in eleven campaigns (D0-D10) twelve days apart. During collections, the surface temperatures of ear base (ET, degrees C) and ocular globe (OGT, degrees C) were measured by infrared thermography, and the subcutaneous temperature (ST, degrees C) was measured with the use of transponder containing an implantable microchip. Rectal temperature (RT, degrees C) was considered as a reference for body temperature. Temperature and Humidity Index (THI), Black Globe Temperature and Humidity Index (BGHI) and Radiant Heat Load (RHL, W/m(2)) were calculated. ET (33.32 +/- 0.12 degrees C), ST (36.10 +/- 0.07 degrees C), OGT (37.40 +/- 0.06 degrees C) and RT (38.83 +/- 0.03 degrees C) differed significantly (P<0.05). There was positive correlation of RT with OGT (r = 0.392), ET (r = 0.264) and ST (r = 0.236) (P<0.05). Considering the bioclimatic indicators, the highest magnitude correlations were observed between ET and THI (r = 0.71), ET and BGHI (r = 0.65), and ET and RHL (r = 0.48). The use of microchip represented a practical method, but with limited predictability. On the other hand, infrared thermography proved to be safe and non-invasive, presenting greater precision for inference of internal body temperature. ET was more influenced by meteorological conditions.
Keywords: Body temperature; RFID; Infrared thermography; Precision livestock; Beef cattle